Associação dos diretores e ex-diretores das escolas da rede pública estadual de ensino do Espírito Santo: formação e atuação de gestores escolares em questão - Ghidini, Carlos Frederico Jordão (2023)
The study aims to understand the constitution process of the Association of Directors and Former Directors of Public Schools of the State Network of Espírito Santo (Adires) and its performance with the managers of public schools of the State Network of Education of Espírito Santo. The Association was created in 2013 to provide administrative and legal support to Education professionals who act/acted as school principals in the Public State Network of Espírito Santo, comprising more than 450 affiliates. Therefore, it adopts as a theoretical reference the works of Freire (1987, 1993, 1996, 2000, 2006, 2015), Chauí (2009, 2012, 2019), Libâneo, Oliveira and Toschi (2012) and Paro (2003, 2005, 2015 , 2016) in the quest to discuss topics such as democracy, school management and democratic management and direct education. Methodologically, it is based on qualitative research and on the assumptions of the case study, assuming the following procedures: a) presentation of the study to Adires and associates and request for data collection; b) analysis of the entity's documents; c) application of a questionnaire by the google form to the directors and associates; d) conducting semi-structured interviews. It elects as participants, the board of directors of Adires, associates (directors and former directors). The data were stored in a field diary, in the google questionnaire itself and in the cell phone that will be used as a voice and image recorder. As a result, the research seeks to contribute to the creation/action of associations aimed at supporting the work of school principals; reflect on new contributions regarding the training of school principals; to strengthen dialogic relations between schools and Departments of Education and to analyze which advances are necessary for the entity, in addition to producing a portfolio on Adires with regard to its constitution, performance and investment in the training of the school director segment.